Analysis of the Influence of Influencer Marketing, Electronic Word of Mouth, and Brand Love on Product Purchase Decisions - Miswanto Miswanto; Anti Aulia Nuri Saragih; Veronica Sunarto Ximenes (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the influence of influencer marketing, electronic word of mouth, and brand love on purchasing decisions on Somethinc skincare products in Yogyakarta. The number of samples involved in this study was 190 respondents with purposive sampling techniques. Data collection techniques are carried out by distributing questionnaires online through Google Forms. Data analysis and hypothesis testing were carried out in this study using the Structural Equation Model (SEM) approach. The results of this study show that influencer marketing variables have a positive and significant effect on purchase decisions, electronic word of mouth has a positive and significant effect on purchase decisions, and brand love has a positive and significant effect on purchase decisions. This study's findings are considered a contribution and an additional source of information for further research in the same scope